“A oficina da nacionalidade”: higienização das crianças e das mães na Parahyba (1911 a 1927) - Rocha, Francineide Rodrigues Passos (2016)
This paper examines the process of cleaning as school practice in the city of North Parahyba, and their contributions through hygienists present speeches in the field of education. We will talk about hygiene, childhood and motherhood through the documents and printed the 1911 period to 1927. The relationship between the topics will be the object of analysis as hygiene linked to school and maternity care have contributed to improving the education of children. Carried out a research in the field of history of education in the press, from three newspapers: A União, The Press and O Educador and the Era Nova magazine. In this discussion, the presence of printed as a source of dissemination of hygiene requirements and the need to stick to the formation of children and the actions developed in primary school, is seen as an improvement of the service tool and consequently attached to economic development the nation. From the theoretical and methodological point of view, dialogue with discussions of power embraced the body control in Michel Foucault. (1997/2013) Speaking of sources to be part of the story from the perspective of Michel Certeau, (2002) to sort, group and reorder these documents consistently, give a new meaning to the set and culture of hygiene in the school space. The contributions of José Gonçalves Gondra, (2000/2003) on the social production of school and the place given to it in the construction of civilized people. The eugenics and hygiene view on the doctor Renato Kehl, (1925/1926/1933) speech, and the alliance and partnership between motherhood and hygiene appreciated by Maria Martha Freire (2009) emphasizes the buildings of hygiene requirements in the social formation of woman as mother. From these theoretical perspective, we understand that the studied speeches show education as a practice of civility, regulation, standardization and docility, concepts used in school for those who venture into the world of Higia.